UV-curable powder transparent coatings based on oligo(meth)acrylic resins - Pojnar, Katarzyna; Pilch-Pitera, Barbara; Kisiel, Maciej; Zioło, Aleksandra; Kędzierski, Michał (Polimery, 2024)
Polyacrylic resins containing glycidyl methacrylate (GMA), methyl methacrylate (MMA) and n-butyl acrylate (BA) in various molar ratios were obtained. Triaryl sulfonium hexafluorophosphate was used as a photoinitiator and reacted with the epoxy groups of GMA. The relationship between the chemical structure of polyacrylic resins and the parameters of the UV curing reaction and the functional properties of powder coatings was investigated. The appearance and mechanical properties of the coatings were determined based on thickness, gloss, roughness, deformability, scratch resistance, adhesion to steel, hardness, and water contact angle. DMA was used to assess the cross-link density. Powder coatings with good physical and mechanical properties and curing time of 70 s were obtained.